Static Binding Force of Forcing Pair of Three Pair Bars Space RCCR Mechanism - Zhuang Sen; Ouyang Kai; Cui Chao; Feng Zhipeng (Jixie chuandong, 2015)
The deformation compatibility equation is built on the basis of the flexible treatment of the forcing pair,and the static binding force of forcing pairs of three pair bars space RCCR mechanism is solved under the condition of close to rigid body.The result is more concise and closing to the ideal state compared with that on the basis of the flexible treatment of the forcing bars.